TikTok dakwah content: A study of religious understanding in Islamic education - Yesi Anggun Susanti; Encu Mulya Syamsul; Ahmad Zacky Burhani (Curricula: Journal of Curriculum Development, 2025)
The success of digital da'wah depends heavily on selecting platforms that match the audience's characteristics. This study employs a descriptive qualitative approach, utilizing interview instruments to analyze and describe the level of understanding and practice of Islamic teachings among Generation Z, as reflected in TikTok da'wah content. Fifty respondents aged 15-25 years were interviewed for this research. The results showed that TikTok is the most widely used social media platform for obtaining religious information among Generation Z, and the majority of respondents demonstrated a solid understanding of and adherence to Islamic teachings as presented in da'wah content on TikTok. Most respondents demonstrated a solid grasp of the da'wah messages and could apply them to their daily lives. On average, respondents reported understanding the da'wah content and its applicability to their daily lives. These findings indicate TikTok's potential as an effective platform for disseminating da'wah content to Generation Z. Delivering religious messages in a concise and interesting manner opens up new opportunities in education and the spread of Islamic values. This research provides initial insight into the positive impact of consuming da'wah content on TikTok on the religious understanding of its users.   Abstrak Keberhasilan dakwah digital sangat bergantung pada pemilihan platform yang sesuai dengan karakteristik audiensnya. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan tingkat pemahaman dan pengamalan ajaran Islam dari konten dakwah TikTok pada generasi Z. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan instrumen wawancara pada 50 responden usia 15–25 tahun. Hasil penelitian menunjukkan bahwa TikTok menjadi platform media sosial yang paling banyak digunakan sebagai sumber informasi keagamaan bagi generasi Z. Mayoritas responden menunjukkan tingkat pemahaman yang baik terhadap pesan-pesan dakwah yang disampaikan, serta mampu mengaplikasikannya dalam kehidupan sehari-hari, rata-rata responden menyatakan memahami isi dakwah, dan dapat mengaplikasikan pesan tersebut dalam kehidupan sehari-hari. Temuan ini mengindikasikan potensi TikTok sebagai platform yang efektif untuk penyebaran konten dakwah di kalangan generasi Z dan menyampaikan pesan-pesan keagamaan secara ringkas dan menarik membuka peluang baru dalam pendidikan dan penyebaran nilai-nilai Islam. Penelitian ini memberikan wawasan awal mengenai dampak positif konsumsi konten dakwah TikTok terhadap pemahaman keagamaan penggunanya. Kata Kunci: konten dakwah; pemahaman keagamaan; pendidikan Islam; TikTok